2015
DOI: 10.1111/jzo.12275
|View full text |Cite
|
Sign up to set email alerts
|

Spotted hyaenas switch their foraging strategy as a response to changes in intraguild interactions with lions

Abstract: Large carnivores are keystone species and their foraging strategies may be a determinant in the functioning of communities and ecosystems. The plastic foraging behaviour of carnivores is likely to be influenced by a suite of factors. Here, we studied spotted hyaena diet during two contrasting periods in terms of lion population abundance to investigate the changes in spotted hyaena foraging strategies in response to changes in expected intraguild interactions in Hwange National Park, Zimbabwe. The analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…How hyaena populations respond in the absence of strong competition from lions is of key interest, and the impact of these hyaena dynamics on prey populations is also unknown and likely significant, particularly since Liuwa hyaenas rely almost exclusively on predation versus scavenging for food acquisition. Several investigators have found complex relationships between lion and hyaena abundance and the relative proportion of scavenging and kleptoparasitism versus predation (Watt and Holekamp 2008, Périquet et al, 2015b and this is likely to be dynamic in a recovering ecosystem. Liuwa's keystone species, the wildebeest, has recovered rapidly from years of poaching; however a strong selection for wildebeest by hyaena, coupled with what may constitute a numerical response by hyaena populations to a growing wildebeest population, is likely to exert a strong limiting influence on the net growth rate and recovery of wildebeest.…”
Section: Top-down Impacts Of Hyaena In the Absence Of Strong Lion Commentioning
confidence: 99%
See 1 more Smart Citation
“…How hyaena populations respond in the absence of strong competition from lions is of key interest, and the impact of these hyaena dynamics on prey populations is also unknown and likely significant, particularly since Liuwa hyaenas rely almost exclusively on predation versus scavenging for food acquisition. Several investigators have found complex relationships between lion and hyaena abundance and the relative proportion of scavenging and kleptoparasitism versus predation (Watt and Holekamp 2008, Périquet et al, 2015b and this is likely to be dynamic in a recovering ecosystem. Liuwa's keystone species, the wildebeest, has recovered rapidly from years of poaching; however a strong selection for wildebeest by hyaena, coupled with what may constitute a numerical response by hyaena populations to a growing wildebeest population, is likely to exert a strong limiting influence on the net growth rate and recovery of wildebeest.…”
Section: Top-down Impacts Of Hyaena In the Absence Of Strong Lion Commentioning
confidence: 99%
“…The hyaena's importance to conservation efforts cannot be understated as it is often the last member of the African large carnivore guild to remain in an ecosystem after other species have been eliminated. Within the diverse large carnivore guilds that typify savannah ecosystems in sub-Saharan Africa, the dominant carnivore species, primarily the hyaena and African lion (Panthera leo), compete with each other (Périquet et al, 2015a(Périquet et al, , 2015b and can have strong limiting effects on the populations of threatened subordinate competitors (e.g., African wild dogs, Lycaon pictus, and cheetahs, Acinonyx jubatus) (Creel andCreel 1996, 2002;Durant, 1998;Swanson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While spotted hyaenas are generalist foragers that exhibit site‐specific dietary compositions (Périquet et al , ), lions seem to favour the same three or four species in savanna ecosystems (e.g. wildebeest, warthog and kudu; Mills, ; Power, ), which was no different for these predators in Selati.…”
Section: Discussionmentioning
confidence: 99%
“…Overall diet composition for each carnivore was determined as FO, calculated as a percentage, and using the number of times a food item was encountered as a function of the total number of occurrences of all food items found (Loveridge & Macdonald, ; Klare et al , ; Périquet et al , ). Reducing the large number of prey species consumed into categories allows for the simplification of descriptions and comparisons of diet (Trites & Joy, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation